A selective harmonic compensation and power control approach exploiting distributed electronic converters in microgrids - dos Santos Alonso, Augusto Matheus [UNESP]; Brandao, Danilo Iglesias; Caldognetto, Tommaso; Marafão, Fernando Pinhabel [UNESP]; Mattavelli, P. (Elsevier, 2020)
This paper proposes an approach to obtain harmonic compensation and power control by exploiting the electronic power converters deployed in low-voltage microgrids. By the proposed approach, distributed harmonic current compensation is achieved without interfering with the converter's power exchange involved in interfacing the local energy resources (e.g., renewable sources, storage devices) with the grid. The control framework refers to a master/slave microgrid architecture where distributed power converters play as slave units, coordinated by a centralized controller; the data exchange among agents occurs periodically, concerns current magnitudes only, and can be fulfilled by communication means of limited performance. The paper shows the achievable results in terms of power quality improvements and discusses the challenges related with the aimed objective. The proposed methodology is evaluated by means of simulation and experimental tests on a single-phase low-voltage microgrid prototype comprising nonlinear loads and two converters. Different cases of generation limits, load variations, voltage levels, voltage distortions, and line parameters are considered in the tests reported. In addition, the robustness of the proposed method to non-ideal and faulty communication links is discussed and shown by means of experimental results.
Keywords: Distributed converters; Harmonic compensation; Hierarchical control; Power quality; Power sharing